Entrenching Waste Hierarchy for Sustainable Municipal Solid Waste Management in Kenya - Kituku, Wambua; Odote, Collins; Okidi, Charles; Kameri-Mbote , Patricia (Journal of Sustainable Development Law and Policy, 2025)
Prioritizing waste prevention, reuse, recycling and recovery of materials and energy over disposal through landfilling, offers the waste hierarchy approach (WHA) a sustainable pathway to the management of municipal solid wastes (MSW) and realization of a circular economy. The concept is now part of the legal framework in some developing countries and its implementation has been credited for addressing waste problems linked to high rates of economic growth and urbanization. Even though Africa Vision 2063 prioritizes improvements in urban waste recycling in the continent, much of the MSW generated on the continent is disposed through landfilling evidencing weak adoption of the WHA. This article contends that because WHA is not adequately incorporated in the current legal framework at national and sub-national levels of government, Kenya is unlikely to achieve a circular economy approach necessary for realizing sustainable waste management. Operationalization of the WHA is impeded by inadequate financing, weak institutional coordination, gaps in private sector and informal actors’ engagement and risks associated with investments in large-scale waste recovery initiatives. It is therefore necessary for Kenya to elaborate the WHA in its legal framework at both national and county level, while ensuring adequate financing, involvement of informal actors, incentivization of private sector and adoption of waste planning procedures.